An Integrated Production Pipeline for 2D Animation in Cultural Heritage Visualization - Dadan Zaliluddin; Tri Ferga Prasetyo; Maulana Ibrahim (Eastasouth Institute, 2025)
The visualization of cultural heritage through digital media has become an effective approach to preserving and disseminating historical narratives to a wider audience. However, the production of 2D animation for cultural heritage visualization often faces challenges related to inconsistent workflows, inefficiencies in production stages, and the lack of structured integration between storytelling and technical animation processes. This study aims to design and implement an integrated production pipeline for 2D animation that supports systematic, efficient, and reproducible development of cultural heritage visualization. The proposed pipeline is structured into three main stages: pre-production, production, and post-production, incorporating storytelling design, visual asset development, animation principles, and compositing techniques. The research adopts a design-based research approach, using a local cultural heritage case study as the implementation context. Data were collected through observation, documentation, and iterative development of animation assets, followed by qualitative evaluation of workflow effectiveness and production consistency. The results demonstrate that the integrated pipeline improves production efficiency, enhances visual coherence, and supports accurate representation of cultural narratives. The proposed framework provides a practical reference for animators, educators, and researchers in developing 2D animation-based cultural heritage visualization. This study contributes to the field of animation production systems by offering a structured pipeline model that bridges technical animation processes with cultural storytelling requirements.